2019
DOI: 10.3390/diseases7010009
|View full text |Cite
|
Sign up to set email alerts
|

The MAPK Signaling Pathways as a Novel Way in Regulation and Treatment of Parasitic Diseases

Abstract: Few major advances in fighting parasitic diseases have been made in China since the development of new methods for prevention, control, and elimination. However, the proportion of immunocompromised individuals has increased due to the growth of chronic diseases, population aging, and more frequent cases of patients with AIDS and cancer. All these problems can promote development of parasitic infections, which is commonly associated with manipulation of host signaling pathways and the innate immune system. Mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…MAPK signaling pathway abnormalities are thought to be closely associated with inflammatory responses [ 39 ]. In addition, the MAPK signaling pathway has a key role in the development and maintenance of parasites in the body of the host and may serve as a new therapeutic target pathway for parasitic disease [ 40 ]. Although the P53 signaling pathway is often used to study cancer-related diseases, in some parasitic infections (e.g., Plasmodium), it can reduce its parasitic burden [ 41 , 42 ].…”
Section: Analysis and Discussion Of Clinical Datamentioning
confidence: 99%
“…MAPK signaling pathway abnormalities are thought to be closely associated with inflammatory responses [ 39 ]. In addition, the MAPK signaling pathway has a key role in the development and maintenance of parasites in the body of the host and may serve as a new therapeutic target pathway for parasitic disease [ 40 ]. Although the P53 signaling pathway is often used to study cancer-related diseases, in some parasitic infections (e.g., Plasmodium), it can reduce its parasitic burden [ 41 , 42 ].…”
Section: Analysis and Discussion Of Clinical Datamentioning
confidence: 99%
“…Four signalling pathways were also enriched in PFR group compared to control group (Figure 7). This enrichment was expected because these pathways are involved in infection like Vascular endothelial growth factor (VEGF) pathway which facilitates interaction between pathogens and host cells [53], the mitogen-activated protein kinase (MAPK) which is important in modulating host and pathogen interactions [54], epidermal growth factor receptor (EGFR) which modulates cell survival, proliferation, differentiation, and migration/invasion [55], and Peroxisome proliferator-activated receptor (PPAR) which gets activated during bacterial infection [53]. The enrichment of all these pathways in PFR may also be associated with the secretions of inflammatory cytokines and host cell apoptosis in response to retinitis in PFR group.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently reported that expression of MAPK gene members changed by Echinococcus multilocularis [56]. In a timely manner, balanced regulation of ERK1/2 and JNK was involved in proliferation and apoptosis of hepatocyte, respectively, because two signaling molecules belong to different MAPK pathway subgroups, such as growth factors and external stimuli [57]. In particular, Tnf-α was concurrently enriched in 11 KEGG pathways and regarded as a monotonically up-regulated gene but not a key hub gene/protein.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the previous studies that parasitic infections could contribute to transcriptional alterations of immune system (complement and coagulation cascades [ 51 ], toll-like receptor (TLR) signaling pathway [ 51 ] and natural killer cell/mediated cytotoxicity [ 39 ]), cell growth/death (cellular senescence [ 52 ] and apoptosis [ 38 ]), signal transduction (MAPK signaling pathway [ 53 ]), and endocrine system (insulin signaling pathway [ 51 ]). However, it is worth to mention that the alterations of these pathways may have no biological significance, considering some pathways are often differentially expressed because mammals have a myriad of related genes, such as TLR signaling transducers and MAPK signaling molecules [ 54 57 ]. The role of TLRs in helminth infections is not clear.…”
Section: Discussionmentioning
confidence: 99%